2018
DOI: 10.1177/1934578x1801300903
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Saponin Fractions from Astragalus verrucosus in Tumor and Non-tumor Human cells

Abstract: Among natural chemicals used as cancer chemo-preventive and/or chemotherapeutic agents, saponins represent one of the most promising and interesting family of compounds. In this work, we aimed to elucidate the biological effects on human cells of six saponin fractions (SFs) obtained from in vitro cultures of Astragalus verrucosus Moris, a poorly characterized species. Interestingly, SF (3) showed a strongly inhibitory effect on the proliferation of human colon adenocarcinoma cell line (HCT116) via activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Astragaloside IV (AsIV), an active ingredient derived from A. membranaceus, is known as a signature compound for its various excellent biological activities (Zhou et al 2012), including anti-in ammatory, antioxidant, neuroprotective and anti-cancer effects(Luo, Wu, and Li 2021; Shahrajabian, Sun, and Cheng 2019). Studies have shown that AsIV is not only an excellent immunomodulator but in some aspects even surpasses ginsenosides (Zheng et al 2020), and is of great value in the treatment of cardiovascular and cerebrovascular diseases, respiratory diseases, diabetes and related complications (Facioni et al 2018; Kwon et al 2021). AsIV, despite its natural origin and excellent effects, has poor solubility and stability, resulting in low value adding products and limiting its direct application in solid formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Astragaloside IV (AsIV), an active ingredient derived from A. membranaceus, is known as a signature compound for its various excellent biological activities (Zhou et al 2012), including anti-in ammatory, antioxidant, neuroprotective and anti-cancer effects(Luo, Wu, and Li 2021; Shahrajabian, Sun, and Cheng 2019). Studies have shown that AsIV is not only an excellent immunomodulator but in some aspects even surpasses ginsenosides (Zheng et al 2020), and is of great value in the treatment of cardiovascular and cerebrovascular diseases, respiratory diseases, diabetes and related complications (Facioni et al 2018; Kwon et al 2021). AsIV, despite its natural origin and excellent effects, has poor solubility and stability, resulting in low value adding products and limiting its direct application in solid formulations.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Natural resources such as plants have long been considered as a source of chemotherapeutic or chemopreventive agents against cancer. 2 − 4 However, due to the increasing resistance of certain tumors and the severe side effects of conventional chemotherapy, new pharmacological molecules are needed. In recent decades, advances in cancer molecular biology have identified several biological compounds capable of inhibiting cancer cell growth with improved efficacy and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a significant universal health issue and one of the leading death causes in the world . Natural resources such as plants have long been considered as a source of chemotherapeutic or chemopreventive agents against cancer. However, due to the increasing resistance of certain tumors and the severe side effects of conventional chemotherapy, new pharmacological molecules are needed. In recent decades, advances in cancer molecular biology have identified several biological compounds capable of inhibiting cancer cell growth with improved efficacy and selectivity. Structural diversity and associated synergistic effects, high efficiency, availability, and excellent biocompatibility are the advantages of plants as medicinal resources.…”
Section: Introductionmentioning
confidence: 99%